Foreign aid to agriculture: Review of facts and analysis - Islam, Nurul (International Food Policy Research Institute, 2011)
This paper seeks to provide a consistent and comparable set of data on the trends in the provision of aid to agriculture over time within the framework of changes in the pattern of sectoral distribution of total development aid. Furthermore, it examines the factors, relating both to the agriculture sector itself and to the priorities and allocation processes of the total aid, which may account for the decline in aid to agriculture over the past two decades or more. It analyzes how in recent years the agricultural sector, as conventionally defined, and investments in the sector are increasingly incorporated in the new and wider concepts of food security and rural development as well as investments in them. In the end, the paper evaluates in the foregoing context the various commitments of the quantitative targets of aid made by the donors in the period following the post-2007 food crisis for agricultural development and food security.